Effect of dislocation cell walls on hydrogen adsorption, hydrogen trapping and hydrogen embrittlement resistance. (15th April 2020) - Chen, Lin; Xiong, Xilin; Tao, Xuan; Su, Yanjing; Qiao, Lijie
Highlights: The hydrogen coverage first increases and then decreases with increasing deformation. The hydrogen embrittlement resistance is improved when materials are experienced a severe deformation. Dislocation cell walls with a sufficiently high dislocation density are proved to be an effective hydrogen trap. Abstract: This study investigated the effects of dislocation patterns introduced by cold rolling deformation on the hydrogen absorption properties, hydrogen trap behaviors and hydrogen embrittlement (HE) resistance for Armco iron under electrochemical charging. The surface hydrogen coverage first increases and then decreases with increasing deformation, and reaches a maximum at 50% deformation. Dislocation cell walls appear when the deformation is greater than 50%. Furthermore, the HE resistance is improved when the deformation reaches 80%. Because the dislocation cell walls can be used as effective hydrogen traps when the dislocation density reaches a sufficiently high value.